Jonas & Kovner's health care delivery in the United States - Kovner, Anthony R.; Knickman, James; Weisfeld, Victoria D.; Jonas, Steven (Health Care Delivery in the United States (Jonas & Kovner's), 2011)
This 10th edition of a classic textbook for graduate and advanced undergraduate students presents the critical issues and core challenges surrounding our health care system. Leading thinkers, educators, and practitioners provide an in-depth and objective appraisal of why and how we organize health care the way we do; the enormous impact of health-related behaviors on the structure, function, and cost of the health care delivery system; and other emerging and recurrent issues in health policy, health care management, and public health. This text is divided into five sections, in order to provide some coherence to this broad terrain. Part I, The Current U.S. Health Care System, addresses major characteristics and issues, including reform, financing, and comparative health care systems. This section now includes multiple new charts and tables providing concrete health care data. Part II, Population Health, focuses on health behavior, including health care models, public health policy and practice, risk factors, facilitating healthy lifestyle practices, and access to care. Part III, Medical Care Delivery, addresses integrated health models, delivering high-quality health care, cost, and value, and comparative effectiveness. Part IV, Support for Medical Care Delivery, concerns governance and management issues, including accountability, the health workforce, and information technology. Part V, The Future of Health Care Delivery in the United States, includes a new 5-year trend forecast.